ANALISIS BREAK EVENT POINT (BEP) SEBAGA ALAT PERENCANAAN PENJUALAN PADA TINGKAT LABA YANG DIHARAPKAN (Studi Kasus PTPN VII UNIT BEKRI TAHUN 2016-2018) - Restu Noviana, Anggie; Suhada, Bambang (DINAMIKA (Jurnal Manajemen Akutansi Bisnis dan Kewirausahaan), 2020)
In business activities in this era of globalization, technological developments are needed to expand business networks. The level of competition that is quite tight makes business actors more innovative in carrying out marketing activities for their products and services. This study aims to determine the effect of promotion through social media and word of mouth on consumer decisions in choosing a wedding organizer. This type of research is quantitative data analysis and in this study using descriptive analysis method to collect data in the field by taking samples from a population of 60 respondents to consumers of Art Project Lampung. Test requirements analysis using normality test, linearity test and homogeneity test. Testing the analysis model using multiple regression models, partial test (t test), simultaneous test (F test), and the coefficient of determination (R2). And using statistical hypothesis testing. Based on the results of research with multiple linear regression analysis with t test, it was found that promotion through social media had a positive and significant effect on consumer decisions to choose a wedding organizer, while word of mouth had a positive and insignificant effect on consumer decisions to choose a wedding organizer. From the F test, it is found that promotion through social media and word of mouth simultaneously has a significant influence on consumer decisions to choose a wedding organizer.